Child Life Protection: Prospects For Improving Ukrainian Legislation - Kovtun, Oleksandr (Archives of Criminology and Forensic Sciences, 2023)
Based on the analysis of both scientific works dedicated to the issues of maternal infanticide and specific provisions of criminal legislation in foreign countries aimed at protecting children’s lives, a set of new insights has been obtained. These insights enable the development of a comprehensive set of measures aimed at protecting the lives of children. As the analysis has shown, in recent years, a number of publications have been published aimed specifically at improving criminal legislation, namely Article 117 of the Criminal Code of Ukraine, including the following works: “Criminal liability for the murder of a newborn child: a comparative legal aspect” (Musychenko O. M., Verbytskyi O. S., 2019), “Current problems of qualification of the murder of a mother of her newborn child” (Zhmur Yu. M., Hotsuliak O. O., 2020), Intentional murder by a mother of her newborn child: controversial issues of qualification. Marysiuk K., Druk S., 2020). However, many problems remained unresolved, primarily regarding the qualification criteria, the moment of determining the beginning of a child’s life, the age limit at which criminal liability for this type of crime arises, and other issues. Preventive measures that will prevent the murder of children are an important area, as they are the most vulnerable part of people. Since human life, including the life of an unborn and newborn child, is realized through the system of criminal law, we consider it necessary, based on the studied foreign legislation, to develop a set of regulations that will allow for the proper protection of the life of a child and bring to justice all persons who facilitate the commission of this type of crime or encourage the mother to commit criminal acts. Given the experience of protecting the life of a child in foreign countries, it is important to remember that the path of persuasion is not the path of prohibition, but the path of persuasion. Of course, persuasion plays an important role in a person’s life, but it is not always effective. As practice shows, if a woman decides to get rid of her unborn child, she will actively do so, both during pregnancy and after birth. Such women will do everything possible to get rid of their newborn child. Therefore, we consider it necessary to take into account the German legislation, which regulates at the legislative level the issues that provide for a number of measures aimed at counseling pregnant women in difficult conflict situations and in need of social support. Also, to increase responsibility for crimes aimed at taking the life of a child. Analyzing the draft of Criminal Code of Ukraine, we came to the generalized conclusion that the beginning of human life does not begin at the moment of physical birth, but much earlier. This conclusion is confirmed by a number of provisions of foreign countries, even those where the murder of a newborn child is a privileged crime. Therefore, the comparative legal analysis of the criminal laws of foreign countries that provide for liability for taking a child’s life allows us to actualize the issues which, in our opinion, will form the basis for further research and improvement of legislation, and thus will improve the activities of judicial, investigative and other bodies, which will generally lead to better protection of human rights.